Kani Koter, Iron Age cemetery from Iranian Kurdistan - Amelirad, Shelir; Azizi, Eghbal (Iran, 2021)
Kani Koter cemetery is located in Iranian Kurdistan, close to Dere Pemeyan (or Persian Dare Panbedan) village, between the ancient sites of Ziwiye and Karafto Cave (Figure 1). In this article, we discuss the material discovered from one of the graves in this cemetery, its chronology, and cultural associations. Unfortunately, tomb robbers plundered this grave, completely ruining the tomb's stratigraphic context. Fortunately, in 2016 the Cultural Heritage Organization of Kurdistan rescued all of the stolen artefacts, and today the collection is stored at the Sanandaj Museum. The grave has yielded a number of elaborately decorated objects that belong nominally to Assyrian, Urartian and Mannaean artistic traditions, with the date for the finds being established by means of comparisons with Assyrian and Urartian artefacts.